ERBB2D16 Expression in HER2 Positive Gastric Cancer Is Associated With Resistance to Trastuzumab - Wang, Shuo; Zhao, Yuze; Song, Yuguang; Qiao, Guoliang; Di, Yan; Zhao, Jing; Sun, Pingping; Zheng, Huixia; Huang, He; Huang, Hongyan (Frontiers in Oncology, 2022)
The human epidermal growth factor receptor-2 (ERBB2; formerly HER2)isoform ERBB2ΔEx16 (ERBB2d16) was oncogenic by mediating epithelial-mesenchymal transition (EMT), immune evasion, and resistance cell death to the anti-HER2 (trastuzumab) therapy. However, its physiological implications in gastric cancer were unclear. In this study, we examined a total of 110 patients with either locally advanced or metastatic HER2+ gastric cancer for the expression of ERBB2d16 and EMT markers, and the infiltration of CD3+ T cells in tumor tissues, and evaluated their relevance with the responses to the standard chemotherapy plus trastuzumab according to the RECIST criteria. We found that the ERBB2d16 isoform was present at a relatively high level in about half of the tumor samples examined (53/110) and an elevated ERBB2d16/ERBB2 ratio was positively associated with the expression of high E-cadherin and low vimentin indicating EMT, and with poor CD3+ T cell infiltration and strong intratumoral expression of programmed death 1 (PD-1) and programmed death ligand 1 (PD-L1) as well as reduced diversity of T cell receptor clones. Moreover, the progression-free survival and overall survival of patients treated with trastuzumab were substantially shorter in those with a high ERBB2d16/ERBB2 ratio. In agreement, analysis by Cox proportional hazards models confirmed that high ERBB2d16 expression was a risk factor associated with an adverse prognosis. Thus, our data fit well with an oncogenic role of ERBB2d16 in gastric cancer by promoting EMT and immunosuppression. We also found that ERBB2d16 expression resists gastric cell death in patients treated with trustuzumab, and the ERBB2d16/ERBB2 ratio may serve as a novel prognostic maker for patients with gastric cancer that receive trastuzumab therapy.